The hemopexin and O-glycosylated domains tune gelatinase B/MMP-9 bioavailability via inhibition and binding to cargo receptors. - Van den Steen, P; Van Aelst, I; Hvidberg, V; Piccard, H; Fiten, P; Jacobsen, C; Moestrup, S; Fry, S; Royle, L; Wormald, M; Wallis, R; Rudd, P; et al. (2006)
Gelatinase B/matrix metalloproteinase-9 (MMP-9), a key regulator and effector of immunity, contains a C-terminal hemopexin domain preceded by a unique linker sequence of approximately 64 amino acid residues. This linker sequence is demonstrated to be an extensively O-glycosylated (OG) domain with a compact three-dimensional structure. The OG and hemopexin domains have no influence on the cleavage efficiency of MMP-9 substrates. In contrast, the hemopexin domain contains a binding site for the cargo receptor low density lipoprotein receptor-related protein-1 (LRP-1). Furthermore, megalin/LRP-2 is identified as a new functional receptor for the hemopexin domain of MMP-9, able to mediate the endocytosis and catabolism of the enzyme. The OG domain is required to correctly orient the hemopexin domain for inhibition by TIMP-1 and internalization by LRP-1 and megalin. Therefore, the OG and hemopexin domains down-regulate the bioavailability of active MMP-9 and the interactions with the cargo receptors are proposed to be the original function of hemopexin domains in MMPs.